Clinical tutoring for nursing students: analysis of the Barletta-Andria-Trani Health Facility experience - Federico Ruta; Michele Massaro; Beatrice Dibenedetto; Valeria Lombardi; Francesca Biscosi; Elena Barile; Gioacchino Dibenedetto; Giuseppe Papagni; Nicola Tortora; Tatiana Bolgeo; Vincenzo Dicuonzo; Mauro Parozzi; et al. (Milano University Press, 2024)
BACKGROUND: University nursing tutoring from clinical nurses is an essential and necessary component in supporting students to be successful in curricular activities in support of classroom learning. The aim of this study was to describe the experience of the nurse involved in clinical tutoring of students in the Bachelor of Science in Nursing course at an Italian university.  METHODS: A survey questionnaire created on the basis of a literature review was sent to all nurses involved in clinical tutoring within the ASL Bt. RESULTS: 67.44% reported that they had never received any kind of specific training despite the fact that 92.51% considered it essential for the correct performance of the role. 82.13% believe that this activity is not adequately valued CONCLUSIONS: The results obtained represent beginning of an educational pathway aimed at standardising the training processes of the clinical tutor, oriented towards improving the learning pathway of the future nursing class.